ANALISIS PENGARUH KESADARAN WAJIB PAJAK PELAYANAN FISKUS DAN TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN - Vernanda Ika D, 12.05.52.0060; Setyowati, Widhy (Students Journal of Accounting and Banking, 2017)
This study examines the effect of awareness of taxpayers, tax authorities and service tax rates on tax compliance in KPP Madya Semarang.this research conducted in KPP Madya Semarang. In this study, the sampel used by 100 responden who are registered as corporate taxpayers in KPP Madya Semarang in 2016. The method used is randome sampling method. The equipment in this study used multiple linier regression, partial test (test t), and test the feasibility of the model. The results of the study showed that the awareness of the taxpayers, the service tax authorities and tax rates influenced as positive toward the tax compliance.Keywords: Awareness Taxpayer, Tax Authorities, Services Tax Rates, Tax Compliance